Maintainer of Aesthetic Space - Functional in Pediatric Dentistry. Case Report - Echevarria, Sandra (2019)
Early loss of deciduous teeth is a common problem in pediatric dentisty, can be associated with traumas of the anterior region of early childhood caries (ECC), ectopic eruption among others, and can cause occlusal damage and other undesirable aesthetic-functional squeal. The preparation of a functional - aesthetic space maintainer device is one of the most used treatment options in this type of condition; Among the indications of this, is the functional, phonetic and aesthetic recovery in order to prevent emotional disorders in children, improve the social aspect and preserve the correct dimensions of the arch, avoiding occlusal disharmonies. Within the main space mantainer devices we the partial anterior prosthesis of the Denari tube-bar system. This clinical case report shows the importance of the esthetic - functional maintainer, the correct preparation and clinical application in early childhood, orienting the professionals who treat pediatric patients.